Ways of Knowing, a Quantitative Analysis of the Intersection between the Women’s Ways of Knowing Model and Perry’s Scheme of Intellectual Development - Carol Eichholz Baron PhD (Adult Education Research Conference, 2006)
This quantitative study looks at the intersection between two epistemological theories: (1) the Women’s Ways of Knowing Model and (2) Perry’s Scheme of Intellectual Development. Findings confirm the existence of ways of knowing structures and show that the theories largely address different meaning making constructs. Some demographic differences were found.
Keywords: Ways of knowing; Perry; Belenky; epistemology; teaching